Asset Transfer of Subsidiary of PT ASKES (Persero) and Its Implications for the Utility of Participant Health Security - Kristian, Adhi (Journal of Indonesian Health Policy and Administration, 2015)
This research aims to learn about PT AJII transformation process as well as the implications of the transfer concerning service delivery to the National Health Insurance beneficiary. This is a normative empirical research, analyzing provision of the prevailing laws, legal principles and of the practice by carrying out library and field research. Informants of the research were the Primary Commissioner of PT AJII, who acted as internal supervisor of the transfer, member of Social Security Agency Bodies, (BPJS) and experts of social security who provided information and solution about the problems researched. The data obtained were analyzed by using qualitative method. Research result indicated that 80 percent shares of PT AJII were acquiesced, resulting in a transfer of control toward the company. The transfer process was problematic, dilemmatic, and potentially illegal. In addition to the three different legal provisions involved, the transfer also had to comply with both the public interest, that was the stakeholder participants, and the private interests, (shareholder of PT AJII). There was a possibility of illegality. It was on 23 of December 2013 that the transfer process of PT AJII was still in the stage of agreement signing, while the whole process had to end before 1 January 2014. This is in accordance with article 60 paragraph (3) of BPJS Law, that on 1 January 2014 PT Askes was no longer exist. All legal acts on behalf of PT Askes, including the transfer of its subsidiary company, remain intolerant because the management of PT Askes had become the management of BPJS. Additionally, it was also found that the transfer could have an implication to the increase of the service capacity of BPJS and the increase of utility for the participants.